0461 Blunted Baroreflex Sensitivity and Reduced Morning Parasympathetic Activity in Sleep-Onset Insomnia. (27th May 2020) - Tsai, H; Kuo, T; Yang, C
Abstract: Introduction: Insomnia is a risk factor for hypertension and cardiovascular events, and this association is strongest for sleep-onset insomnia. However, little is known about insomnia on cardiovascular modulation, especially soon after morning awakening, the peak period of time for cardiovascular incidents. This study explored morning cardiovascular function in individuals with sleep-onset insomnia by analysing heart rate variability, blood pressure variability, and baroreflex sensitivity. Methods: Sleep structure of the participants (15 good sleepers and 13 individuals with sleep-onset insomnia) was measured by laboratory polysomnography, followed by continuous recordings of the participant's blood pressure and heart rate for 10 min in the morning. Results: When compared to the good sleepers, the insomnia group showed significant reductions in total sleep time, a longer sleep-onset latency, and reduced sleep efficiency. The sleep structure, including durations of sleep stages, numbers of awakenings and arousal index did not differ between the groups. After morning awakening (averaged time: 12.33 ± 10.48 min), the shorter R-R intervals, lower total power, and lower high-frequency power of heart rate variability were observed among individuals with sleep-onset insomnia, compared with good sleepers. Elevated slopes of systolic and diastolic blood pressure, as well as lower baroreflex sensitivity, were also shown in the insomnia group. Indices of sympathetic activity, including low-frequency percentage of heart rate variability or low-frequency power of blood pressure variability, did not differ between the groups. Conclusion: Weak vagal activity and blunted baroreflex sensitivity were evident among sleep-onset insomnia. These findings indicate difficulty in initiating sleep, without significant sleep fragmentation, can independently affect morning cardiovascular function. This study provides a possible link between sleep-onset insomnia and risk of cardiovascular events. Support: N/A